THE INFLUENCE OF FAMILY ENVIRONMENT AND ENTREPRENEURIAL LITERACY ON ENTREPRENEUR BEHAVIOR OF PMW STUDENTS: Pengaruh Lingkungan Keluarga Dan Literasi Kewirausahaan Terhadap Perilaku Wirausaha Mahasiswa Penerima PMW - Suci Ramadhani; Yuhendri LV (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
The entrepreneurial behavior exhibited by students who receive the UNP PMW remains suboptimal. This resaerch aim to investigate the effects of family environment and entrepreneurial literacy on the entrepreneurial behavior of these students, both independently and in combination. A quantitative approach utilizing a causal research design is applied, with proporetional random sampling as the chosen sampling technique. The research instrument includes a questionnaire to measure the family environment and entrepreneurial behavior variables, along with a set of questions to assess entrepreneurial literacy. Data analysies is conducted through multiple linear regression. The results reveal a significant combined effect of both family environment and entrepreneurial literacy on the entrepreneurial behavior of PMW UNP recipient students. Furthermore, both family environment and entrepreneurial literacy have a notable individual impact on entrepreneurial behavior. The study concludes that improving both the family environment and entrepreneurial literacy is crucial for fostering better entrepreneurial behavior among these students